2017
DOI: 10.1007/s10571-017-0526-9
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 Inflammasome: An Important Driver of Neuroinflammation in Hemorrhagic Stroke

Abstract: Hemorrhagic stroke is a devastating clinical event with no effective medical treatment. Neuroinflammation, which follows a hemorrhagic stroke, is an important element that involves both acute brain injury and subsequent brain rehabilitation. Therefore, delineating the key inflammatory mediators and deciphering their pathophysiological roles in hemorrhagic strokes is of great importance in the development of novel therapeutic targets for this disease. The NOD-like receptor family pyrin domain-containing 3 (NLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…44,46 The inflammasome acts as the master-regulator of IL-1b and facilitates the innate immune response after CNS injury. 26,[56][57][58] Our results show increased levels of NLRP3 inflammasome proteins (NLRP3, caspase-1, and ASC) acutely after injury, indicating that activation of the NLRP3 inflammasome plays a significant role inducing the innate immune response after PTBI. In addition to NLRP3, other inflammasomes such as the NLRP1 also may activate after injury.…”
mentioning
confidence: 58%
“…44,46 The inflammasome acts as the master-regulator of IL-1b and facilitates the innate immune response after CNS injury. 26,[56][57][58] Our results show increased levels of NLRP3 inflammasome proteins (NLRP3, caspase-1, and ASC) acutely after injury, indicating that activation of the NLRP3 inflammasome plays a significant role inducing the innate immune response after PTBI. In addition to NLRP3, other inflammasomes such as the NLRP1 also may activate after injury.…”
mentioning
confidence: 58%
“…In addition, inflammasomes are sensitive to stimulations by internal disturbance, such as misfolded or aggregated proteins and aberrant products of energy metabolism, broadening the range of inflammation inducers beyond infectious stimuli ( 90 ). In ischemic or hemorrhagic stroke models, expression of the NLRP3, a known microglial inflammasome ( 91 , 92 ) component, was increased, and specific blockade of NLRP3 reduced stroke induced neural damage and functional deficits ( 93 , 94 ). Several NLRP3 component proteins were also induced in the pathological tissues in Alzheimer’s disease ( 95 ).…”
Section: The Promises and Limitations Of The Inflammatory Paradigmmentioning
confidence: 99%
“…Previous research has indicated that high levels of ROS under multiple kinds of cellular stress, particularly those produced by mitochondria (mtROS), activates the NLRP3 inflammasome signal pathway (71)(72)(73)(74). In detail, high levels of ROS induce the ROS scavenging protein thioredoxin resolving from thioredoxin interacting/inhibiting protein (TXNIP), which then directly binds with NLRP3 proteins and modulates its assembly via oligomerization (75)(76)(77). Although several investigations have demonstrated that TXNIP is necessary for NLRP3 inflammasome assembly, a cell type-specific modulation of TXNIP occurs, which limits its mediation of inflammatory response ROS signaling pathway activation to particular cell types (78)(79)(80).…”
Section: Activation Of the Nlrp3 Inflammasome Pathway In Ischemic Strokementioning
confidence: 99%